A preliminary report on aural hematoma management with auricular pillow method (2013)
Background: Aural hematoma management is associated with auricular cartilage scarification, pinna deformity and recurrence which are unacceptable dogs’ owners. A simple management method with minimal anesthetic requirement and postoperative patient’s stress, coupled with reasonable management cost and acceptable cosmetic outcomes is presented. Method and findings: Dogs presented at the Veterinary Teaching Hospital, University of Ibadan, Nigeria, with aural hematoma from January 2012-January 2013 were enrolled. Each hematoma was incised, drained and the pinna packed over cotton padded hard core as auricular pillow and supported with a non-adherent compression bandage over the head between 7-12 days. The surgical outcome of this method was compared with conventional methods used previously from 2002-2011 in the same hospital. The pinna healed with least scarification and restored morphology. The method has a comparative anesthetic, patient stress and cost advantages over other conventional methods. Conclusion: The auricular pillow method of aural hematoma management could be a better approach to the management of aural hematoma which is still a challenge in most clinical setting